Predict Burnout With Psychological Capital And Religious Coping - Naera Zhafira Azkiati Z; Agus Abdul Rahman; Irfan Fahmi (Psikis : Jurnal Psikologi Islami, 2019)
Burnout is a psychological phenomenon that should be avoided. However, the phenomenon of burnout still often occurs in the world of work, as experienced by nurses in a private hospital in the city of Bandung. This study aims to predict burnout by using psychological capital and religious coping. The participants were 83 nurses in a private hospital in Bandung. Data were collected using the Psychological Capital Questionnaire (PCQ) from Lututhans, the RCOPE scale from the Pargament, and the Maslach Burnout Inventory (MBI) from Maslach. The collected data were analyzed using multiple regression analysis with Psychological Capital and Religious Coping as predictor variables and Burnout as criterion variables. The results showed that psychological capital and religious coping simultaneously or individually had a negative effect on burnout. Thus, the high and low levels of burnout experienced by nurses can be partially predicted using the extent of psychological capital and religious coping they have